PERANCANGAN DAN IMPLEMENTASI REAL TIME OPERATING SYSTEM PADA SISTEM KENDALI SUHU KANDANG AYAM SECARA CLOSED LOOP - Saputra, Dede Irawan; Permana, Rizki Adika (Journal of Energy and Electrical Engineering, 2022)
Most of the chicken breeders still use manual methods to regulate the temperature in the chicken coop, resulting in uncontrolled temperatures. So that during the brooding period, the chicken's physical condition is still weak and the organs of the body are still not functioning optimally so that they still need heating will be disturbed. Warming during brooding can use incandescent lamps. The heating required for brooding chickens has a range of 27° - 33° Celsius. Therefore made a system that can control the temperature with a faster response. The design of the chicken coop incubator uses RTOS to get a faster response. Real Time Operating System (RTOS) used to give priority scheduling to the chicken coop incubator system. The microcontroller will process the input data using the LM33 sensor, control the AC light dimmer module, and provide data on the LCD. Transfer function modeling using System Identification (SIT) and simulation design using Simulink Matrix Laboratory (MATLAB) software. The system in the chicken coop incubator realized using the RTOS system in the design. Comparison of the simulation results with the implementation of the time constant has a difference of 79 seconds in the open loop and 63 seconds in the close loop resulting in a time delay of the control response. The response time in the use of RTOS is faster in taking the temperature by 52.20 µs and dimmer control by 26.89 µs. However, the response time on the appearance of the data is longer by 5.34 µs.